2007
DOI: 10.1016/j.jmmm.2007.03.212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spin non-collinearities in magnetic nanoparticles

Abstract: In a many-spin approach that takes account of the internal structure, microscopic interactions and single-site anisotropies, we investigate the effect of spin non-collinearities induced by the boundary and surface anisotropy on the behaviour of individual magnetic nanoparticles. Through analytical and numerical calculations, we show that there are mainly two regimes separated by some critical value of the surface anisotropy constant $K_s$ which controls the intensity of spin non-collinearities: i) the so cal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 24 publications
(36 reference statements)
0
39
0
Order By: Relevance
“…47 Later it was shown that 49,50 in fact the effective energy of the many-spin particle is a polynomial in the components of its net magnetic moment. This polynomial can be, with a fairly good approximation, limited to a sum of a quadratic and a quartic contribution with coefficients that change in sign and magnitude with the intrinsic properties of the particle, namely its size, shape, underlying lattice structure, and physical parameters such as the exchange coupling and on-site core and surface anisotropy.…”
Section: A Energymentioning
confidence: 99%
See 3 more Smart Citations
“…47 Later it was shown that 49,50 in fact the effective energy of the many-spin particle is a polynomial in the components of its net magnetic moment. This polynomial can be, with a fairly good approximation, limited to a sum of a quadratic and a quartic contribution with coefficients that change in sign and magnitude with the intrinsic properties of the particle, namely its size, shape, underlying lattice structure, and physical parameters such as the exchange coupling and on-site core and surface anisotropy.…”
Section: A Energymentioning
confidence: 99%
“…(2). This effective potential comprises a cubic anisotropy contribution, with the coefficient ζ , [47][48][49][50] that accounts for the surface anisotropy. The latter is initially modeled in the many-spin description of a nanocluster with the help of Néel's model for atomic spins.…”
Section: Assembly Of Eosp Clusters: Surface Anisotropy Versus Ddismentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the correction ψψ is the solution of the Helmholtz equation with boundary conditions [66] Δ À k 2…”
Section: Crossover From a Many-spin To A Macrospin Approachmentioning
confidence: 99%